Triazole-Resistance in Environmental Aspergillus fumigatus in Latin American and African Countries - Agustin Resendiz-Sharpe; Klaas Dewaele; Rita Merckx; Beatriz Bustamante; Maria Celeste Vega-Gomez; Miriam Rolon; Jan Jacobs; Paul E. Verweij; Johan Maertens; Katrien Lagrou (Journal of Fungi, 2021)
Triazole-resistance has been reported increasingly in Aspergillus fumigatus. An international expert team proposed to avoid triazole monotherapy for the initial treatment of invasive aspergillosis in regions with >10% environmental-resistance, but this prevalence is largely unknown for most American and African countries. Here, we screened 584 environmental samples (soil) from urban and rural locations in Mexico, Paraguay, and Peru in Latin America and Benin and Nigeria in Africa for triazole-resistant A. fumigatus. Samples were screened using triazole-containing agars and confirmed as triazole-resistant by the European Committee on Antimicrobial Susceptibility Testing (EUCAST) broth dilution reference method. Isolates were further characterized by cyp51A sequencing and short-tandem repeat typing. Fungicide presence in samples was likewise determined. Among A. fumigatus positive samples, triazole-resistance was detected in 6.9% (7/102) of samples in Mexico, 8.3% (3/36) in Paraguay, 9.8% (6/61) in Peru, 2.2% (1/46) in Nigeria, and none in Benin. Cyp51A gene mutations were present in most of the triazole-resistant isolates (88%; 15/17). The environmentally-associated mutations TR34/L98H and TR46/Y121F/T289A were prevalent in Mexico and Peru, and isolates harboring these mutations were closely related. For the first time, triazole-resistant A. fumigatus was found in environmental samples in Mexico, Paraguay, Peru, and Nigeria with a prevalence of 7–10% in the Latin American countries. Our findings emphasize the need to establish triazole-resistance surveillance programs in these countries.